Adaptation of digital signal processing methods to the analysis of speech in neurological pathologies - T. P. Kul; Y. N. Rushkevich; S. A. Lihachev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The methodical and software for the speech signal analysis at neurological pathologies, in particular, bulbar violations, has been offered. The approach is based on the digital signal processing methods adapted to the problem of speech analysis in clinical medicine. The result is a program developed in MatLab that performs the calculating and plotting spectrogram, histogram, kepstrogramm, frequencies of the main tone for the recorded speech tests. Approbation of the method was performed on the basis of Republican research and clinical center of neurology and neurosurgery and showed the prospects of its use for the diagnosis of bulbar syndrome.